2019
DOI: 10.3389/fnhum.2019.00372
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Structure in Haptic Signaling Under a Cooperative Task

Abstract: Haptic communication between humans plays an important role in society. Although this form of communication is ubiquitous at all levels of society and of human development, little is known about how synchronized coordination of motion between two persons leads to higher-order cognitive functions used in communication. In this study, we developed a novel experimental paradigm of a coin-collecting task in which participants used their hands to control a rod to jointly collect the coins on the screen. We characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…In the light of the previous study 30 , we, also, identified haptic states to further understand the force interactions. As can be seen from Fig.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…In the light of the previous study 30 , we, also, identified haptic states to further understand the force interactions. As can be seen from Fig.…”
Section: Resultsmentioning
confidence: 98%
“…It is important to note that when paired participants apply a force at the same time to interact with their partner and environment, a haptic channel is created. Based on previous study 30 , we quantified the following outcome measure:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been speculated that the internal force in inter-personal coordination could be a means to form a ‘haptic channel’ that facilitates haptic communication for enabling estimation of the partner’s goal 7 , 11 , 21 23 , such that it could compensate for lack of complete information about the other agent’s effector. A recent study found that the temporal structure of haptic signals is much more complex in dyads than that found in bimanual coordination 24 . Our finding of strong correlation between internal force and inter-agent movement delay provides additional evidence in support of the above theory, suggesting better action/perception coupling via haptic communication is associated with larger inter-personal forces.…”
Section: Discussionmentioning
confidence: 93%
“…Holder, Krishnamurthi, and Theadom [24] have effectively shown the contrasting results that occur when persons who have had a stroke engage in goaloriented activities that are directly connected to tangible items, as opposed to engaging in activities with more conceptual objectives. Thorne et al [25] investigated a task where participants used one hand to collect coins from a table and transfer them to the other hand. Both able-bodied individuals and stroke patients participated in the study, sometimes using money and at other times imitating the action without currency.…”
Section: Motor Learningmentioning
confidence: 99%